The Role of An Experimental Model of Atherosclerosis: apoE-knockout Mice in Developing New Drugs against Atherogenesis - Jawien, Jacek (Current Pharmaceutical Biotechnology, 2012)
Although atherosclerosis was previously thought to be mainly a degenerative disease, it is now well ascertained that its pathogenesis is inflammatory. There was a pivotal role of apoE-knockout mice in understanding the inflammatory background of atherosclerosis. Currently, atherosclerosis is known as a chronic inflammatory disease, in most cases initiated by hypercholesterolemia. Recently, the mouse has become the best model for experimental atherosclerosis. It was in 1992 that the first line of gene targeted mice, namely apolipoprotein E-knockout mice was developed. The apoE-deficient model develops extensive atherosclerotic lesions on a chow diet. The LDL receptor - deficient model has elevated LDL levels, but no lesions, or only very small lesions, form on the chow diet. However, robust lesions do form on the westerntype diet. The creation of apoE- knockout mice has changed the face of atherosclerosis research. Gene-targeted mouse models has changed the face of atherosclerotic research and helped in creation of the new theory of atherosclerosis: as an inflammatory disease. Recently, the mouse has become the best model for experimental atherosclerosis. It was in 1992 that the first line of gene targeted mice, namely apolipoprotein E-knockout mice was developed. The apoE-deficient model develops extensive atherosclerotic lesions on a chow diet. It is also the model in which the lesions have been characterized most thoroughly. The lesions develop into fibrous plaques; however, there is no evidence that plaque rupture occurs in this model. The LDL receptor - deficient model has elevated LDL levels, but no lesions, or only very small lesions, form on the chow diet. However, robust lesions do form on the western-type diet. The creation of apoE-knockout mice has changed the face of atherosclerosis research. Gene-targeted mouse models has changed the face of atherosclerotic research and helped in creation of the new theory of atherosclerosis: as an inflammatory disease. Nowadays, apoE- knockout mice model is therefore used in developing new drugs against atherosclerosis. This review describes how new groups of agents are searched.
Keywords: Atherosclerosis